2016
DOI: 10.15406/jpcpy.2016.05.00283
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distress and Life Satisfaction among University Students

Abstract: The objective of the present study is to determine the relationship between psychological distress and life satisfaction among university students. The sample of the present research consisted of 398 university students from three faculties (Medical sciences n=133 Social science n=133 and Engineering n=132). Data was collected from different organizations following the purposive sampling technique. After taking the consent from the participants, the depression Anxiety stress scale (DASS) and life satisfaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 18 publications
2
41
2
2
Order By: Relevance
“…Around the world, research shows that, high level of psychological problem are found in college student, more than 50% of them reported depression symptoms right after their study started. Research in North America and Europe all of them shows fact higher than average population (Kumar, 2016).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Around the world, research shows that, high level of psychological problem are found in college student, more than 50% of them reported depression symptoms right after their study started. Research in North America and Europe all of them shows fact higher than average population (Kumar, 2016).…”
Section: Introductionmentioning
confidence: 94%
“…From there faculties, Engineering, Medical and Social Sciences, college students who attend medical school have higher level psychological distress (Kumar, 2016). They experienced quite large psychological disorder in the early process of their term.…”
Section: Introductionmentioning
confidence: 99%
“…Spiritual well-being memiliki pengaruh yang positif terhadap mental health (Koenig, 2012). Mental health merupakan salah satu faktor yang paling penting dalam menentukan kepuasan hidup mahasiswa, karena individu-individu yang memiliki mental health yang lebih baik mereka akan lebih puas dengan hidup mereka (Kumar, Shaheen, Rasool, & Shafi, 2016). Kepuasan hidup memiliki hubungan yang negatif dengan depresi, kekuatiran dan kesepian, dan memiliki hubungan yang positif dengan kesehatan (Samaranayake, Arroll, Fernando, 2014).…”
Section: Pembahasanunclassified
“…Most of the research found that university students' satisfaction with life and have negative correlation with depression. Their ndings suggest that to improve the satisfaction with life is to focus on the effective intervention and manage depression issue among the university students [19,20].…”
Section: Introductionmentioning
confidence: 99%